ISLAM INDONESIA: DIALOG DUA KEBUDAYAAN (Studi Perbandingan Antara Budaya Islam dan Kepercayaan Kebatinan Asli Indonesia) - Ahmad Saepudin (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
The purpose of writing this article is to describe a comparison between Islamic culture and native Indonesian beliefs. Indonesian society is a society that is part of a group inseparable as long as the civilization between culture and Native beliefs, Islam was born through the Prophet Muhammad, who was present as part of culture is certainly difficult to be separated directly from people who already had the concept of original beliefs before. Keywords: Culture; Belief; Esotherm